Consumer Response to Corporate Hypocrisy From the Perspective of Expectation Confirmation Theory - Zhigang, Wang; Lei, Zhang; Xintao, Liu (Frontiers in Psychology, 2020)
Corporate social responsibility (CSR) can induce consumers’ hypocrisy perception, consequently triggering their negative response to CSR. This study investigate the how consumers’ hypocrisy perception towards CSR is formed and how it leads to consumers’ negative response to CSR from the perspective of expectation confirmation theory. The findings may be summarized as follows. First, consumers’ expectation and performance perception to CSR can affect their hypocrisy perception to CSR. Second, consumers’ CSR performance perception and hypocrisy perception to CSR can affect their negative emotions. Third, consumers’ negative emotions can affect their attitude and negative behaviors to the firm. The finding indicates that consumers’ expectation on CSR and their perception of CSR performance are important for the formation of consumers’ hypocrisy perception to CSR. Consumers’ negative emotions play a vital role in their response to corporate hypocrisy. The contribution to the study of corporate and management implications are discussed.